Polyimide film with low dielectric loss and high thermal conductivity and manufacturing method thereof
By combining copolymerized polyamic acid and thermally conductive particles, a polyimide film with low dielectric loss and high thermal conductivity is prepared, which solves the problems of high dielectric loss and insufficient thermal conductivity in high-frequency and high-speed applications of polyimide films. It achieves better thermal conduction and dielectric properties and is suitable for 5G high-frequency materials.
Patent Information
- Application Number
- CN202310734601.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
AI Technical Summary
The existing polyimide films have high dielectric loss and insufficient thermal conductivity in high-frequency and high-speed applications, resulting in overheating of components and difficult to meet the needs of high-frequency communication.
Copolymerized polyamic acid is prepared by chemical cyclization method, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and specific diamines are added, and thermally conductive particles such as alumina, boron nitride, etc. are added to form a low Polyimide film with high dielectric loss.
A polyimide film with a dielectric loss less than 0.007 and a thermal conductivity greater than 0.35w/mk is realized. It is suitable for high-frequency materials and improves the thermal conductivity and dielectric characteristics of the components.
Smart Images

Figure CN119161575A_ABST
Abstract
Description
Technical Field
[0001] The present application is a polyimide film with low dielectric loss and high thermal conductivity and a method for manufacturing the same, particularly a polyimide film used in high-frequency materials with high thermal conductivity to increase the material's applicability. Background Art
[0002] In recent years, 5G technology has gradually become popular. With the overall demand for greatly improved functional integration, resolution, response speed, and storage capacity of terminal application consumer electronic products, the design performance of electronic products has developed in the direction of high power, high integration, and lightness. The development of flexible board technology has also developed in the direction of high frequency, high speed, and functionality. High-frequency flexible boards are already one of the trends in flexible board technology, mainly used for the enhancement and integration of the functions of mobile communication electronic products. Substrate materials with low dielectric and low transmission loss will be the main focus of subsequent high-frequency material development.
[0003] In addition, 5G network technology is composed of frequency-modulated millimeter waves, but millimeter waves are easily blocked by buildings and easily absorbed by gases, plants and rain in the atmosphere. Millimeter waves have limited transmission range and require the installation of thousands of small base stations for transmission. It is even necessary to increase the transmission power and increase the power consumption of equipment components in order to maintain the transmission distance and smoothness. In addition, the miniaturization of electronic components and equipment and the increase in circuit density will increase the working power consumption and heat generation while processing large amounts of data at a high speed. In order to avoid component failure caused by overheating, the heat dissipation method for the heat generated in the components or equipment is also valued, in order to deal with its waste heat technology.
[0004] Polyimide has excellent heat resistance, electrical properties and mechanical strength properties, and has low dielectric loss after design, so polyimide film is often used in flexible circuit board applications with high temperature processes, and more recently designed in 5G high-frequency and high-speed application components. Generally speaking, the common polyimide film formula is 1,2,4,5-benzene tetracarboxylic anhydride (PMDA) and phenylenediamine (PDA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and p-phenylenediamine (PDA). After adjusting the proportions, good mechanical properties, excellent heat resistance and dimensional stability can often be achieved, so it is preferably used in flexible printed circuit boards, protective films for semiconductor components, interlayer insulation films for integrated circuits, etc. However, the dielectric loss factor (Df) of this type of polyimide film is usually around 0.03 to 0.015, which is not suitable for high-speed and high-speed flexible board applications.
[0005] As the insulating layer of the flexible printed circuit board, the thermal conductivity of the polyimide film is relatively poor. The thermal conductivity of the general polyimide film is about 0.1-0.25w / mk. If it is used in a high-frequency and high-speed flexible board, its poor thermal conductivity will prevent the waste heat generated by the component from being conducted and dissipated in real time, resulting in overheating of the component and poor communication. Therefore, in order to meet the application requirements of high frequency and high speed, the substrate must have good dielectric properties and good thermal conductivity at the same time, which is a problem that needs to be solved.
[0006] The current way to increase thermal conductivity is to add thermal conductive particles. Although the addition can significantly improve the thermal conductivity, thermal conductive particles are usually metal oxides or inorganic substances, etc. This type of material has a high dielectric loss factor, which is not conducive to the application of 5G flexible boards. Therefore, the addition ratio of thermal conductive fillers needs to be properly adjusted with the dielectric properties of the substrate itself to achieve high-frequency and high-speed communication applications.
[0007] The present application uses a specific polyimide film formula composition, and achieves the low dielectric loss and high thermal conductivity characteristics required by high-frequency materials by adding thermally conductive particles, thereby greatly improving its application characteristics. Summary of the invention
[0008] In order to solve the above-mentioned deficiencies in the art, the present application aims to provide a high thermal conductivity polyimide film with low dielectric loss and a method for manufacturing the same, which is prepared from copolymerized polyamic acid via a chemical cyclization method, wherein the copolymerized polyamic acid must at least have a composition of 3,3',4,4'-biphenyltetracarboxylicdianhydride (BPDA) and a diamine of the following chemical formula (A).
[0009] Chemical formula (A):
[0010]
[0011] Wherein in the chemical formula (A), R may be -CF3 or -CH3;
[0012] The molar number of BPDA must account for more than 30% of the total molar number of the dianhydride of the polyamic acid, and the molar number of the chemical formula (A) must account for more than 30% of the total molar number of the diamine of the polyimide acid, and thermal conductive particles are added, and the weight of the thermal conductive particles accounts for 25-50wt% of the film, so that the polyimide film has:
[0013] a. Dielectric loss tangent Df (@10GHz) less than 0.007
[0014] b. Thermal conductivity is greater than 0.35w / mk. DETAILED DESCRIPTION
[0015] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0016] It is particularly important to point out that similar substitutions and modifications made to the present application are obvious to those skilled in the art, and they are all deemed to be included in the present application. Relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present application to implement and apply the technology of the present application. Obviously, the described embodiments are only some embodiments of the present application, not all embodiments.
[0017] If no specific conditions are specified in this application, the preparation shall be carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials or excipients used, as well as the reagents or instruments used, for which the manufacturers are not specified, are all conventional products that can be obtained commercially.
[0018] The application is described in detail below.
[0019] The present invention discloses a high thermal conductivity polyimide film with low dielectric loss and a method for manufacturing the same. The polyimide film is prepared from a copolymerized polyamic acid by a chemical cyclization method, wherein the copolymerized polyamic acid at least comprises 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and a diamine of the following chemical formula (A), wherein the chemical formula (A) is as follows:
[0020]
[0021] The molar number of BPDA must account for more than 30% of the total molar number of dianhydride of the copolymerized polyamic acid; the molar number of chemical formula (A) must account for more than 30% of the total molar number of diamine of the copolymerized polyamic acid to form a reaction composition; the dielectric loss tangent Df (@10GHz) is less than 0.007, and the thermal conductivity is greater than 0.35w / mk.
[0022] Wherein, R in the chemical formula (A) may be CH3, so that the chemical formula (A) is 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB).
[0023] Wherein, R in the chemical formula (A) may be CF3, so that the chemical formula (A) is 2,2-bis(trifluoromethyl)diaminobiphenyl (TFMB).
[0024] The aromatic polyamic acid may include the following aromatic diamines and dianhydrides in addition to the aromatic diamines and dianhydrides of the chemical formula (A) and BPDA:
[0025] The aromatic diamines include: 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 2,2'-bis[4-(4-aminophenoxyphenyl)]propane (BAPP), 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane (HFBAPP), p-phenylenediamine (PDA), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether (6FODA), 4,4'-diaminodiphenyl sulfone (44DDS), 4,4'- Oxydiaminodiphenylene oxide (ODA), 4,4'-diaminobenzanilide (44DABA), 2,2-bis(4-aminophenyl)hexafluoropropane (Bis-A-AF), m-phenylenediamine (mPDA), 3,5-diaminobenzoic acid (35DABA), 2-(4-aminophenyl)-5-aminobenzoxazole (5BPOA), 1,4-bis(4-aminophenoxy)benzene (TPEQ), 4,4'-[1,4-phenylbis(oxy)]bis[3-(trifluoromethyl)aniline] (FAPB), 1,3-bis(4'-aminophenoxy)benzene (TPER);
[0026] The aromatic dianhydrides include: 1,2,4,5-benzene tetracarboxylic anhydride (PMDA), 3,3',4,4'-biphenyl tetracarboxylic anhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic anhydride (BTDA), 3,3,4,4-diphenyl sulfone tetracarboxylic anhydride (DSDA), 2,3,3',4'-biphenyl tetracarboxylic anhydride (α-BPDA), 4,4-hexafluoroisopropylphthalic anhydride (6FDA), 4,4'-(4,4'-isopropyldiphenyloxy) diphthalic anhydride (BPADA), 5-Isobenzofurancarboxylic acid, 1,3-dihydro-1,3-dioxo-,1,4-phenylene ester(TAHQ), N,N'-(2,2'-Bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)bis(1,3-dioxo-1,3-dihydroxybenzofuran-5-carboxamide)(TA-TFMB).
[0027] The chemical cyclization method is formed by adding a dehydrating agent and a catalyst, wherein the dehydrating agent is acetic anhydride, and the catalyst is methyl pyridine and isoquinoline. The amount of the dehydrating agent added is at least 2.7 equivalents, and the amount of the catalyst added is at least 1.2 equivalents. In order to increase its thermal conductivity, thermally conductive particles are added therein, and the thermally conductive particles can be high thermal conductivity filling materials such as aluminum oxide (Al2O3), boron nitride (BN), aluminum nitride (AlN), silicon carbide (SiC), silicon dioxide (SiO2), etc., and their weight accounts for 25-50wt% of the film. It not only has low dielectric loss but also better thermal conductivity, and has better applicability in high-frequency components.
[0028] <Detection method>
[0029] The thermal and electrical properties of the polyimide films obtained in the following examples were measured using the following methods.
[0030] (1) Dk & Df @ 10 GHz: measured using the E5071C ENA Network Analyzer from Keysight Technologies.
[0031] (2) Tg: measured using a Q400 TMA instrument from TA Instruments. The heating rate was set at 10°C / min. In order to remove the stress caused by the heat treatment, the residual stress was removed by the first measurement, and the second measurement result was used as the actual value.
[0032] (3) Thermal conductivity: using the steady-state method (ASTM-D5470)
[0033] <Example 1>
[0034] Production of polyamic acid
[0035] 11.898 grams of p-phenylene diamine (PDA, 0.0110 mole) was added with 400 grams of N, N-dimethylacetamide (DMAc). After all the mixture was dissolved, 16.186 grams of 3,3',4,4'-biphenyltetracarboxylicdianhydride (BPDA, 0.055 mole) was added. The mixture was stirred for reaction for 1 hour while the temperature was maintained at 25°C. Then 23.358 grams of 2,2'-diMethyl-4,4'-diaMinobiphenyl (m-Tolidine, 0.110 mole) was added and stirred until the mixture was completely dissolved. Then 47.586 grams of BPDA, 0.1161 mole, was slowly added and stirred for 12 hours while the mixture was dissolved and reacted. The temperature of the solution was maintained at 25°C. Finally, a small amount of BPDA was used to adjust the viscosity to 200,000±30,000 cps. Finally, a copolymerized polyamide acid solution with a solid content of 20 wt% was obtained.
[0036] Preparation of thermal conductive particle slurry:
[0037] Boron nitride with a particle size distribution of 0.2um-15um was selected and mixed with DMAc to control the solid content of the boron nitride to 20wt%, and then 1.1wt% of polyamic acid was added to the weight of the boron nitride, and the mixture was evenly mixed and then dispersed.
[0038] Preparation of polyimide film
[0039] The above-mentioned polyamic acid is taken to add boron nitride slurry, and the boron nitride content of the high thermal conductivity polyimide film is adjusted by the amount of boron nitride slurry used, and the amount of boron nitride added is controlled to be 25wt% of the weight fraction of the high thermal conductivity polyimide film. After the polyamic acid and boron nitride are evenly mixed, catalysts acetic anhydride and picoline are added to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and lateral shrinkage is performed (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the lateral shrinkage ratio, that is, the wet film width: the dry film width is controlled to be 1:0.80.
[0040] The polyimide film prepared above has a thermal conductivity of 0.38w / mk, a dielectric loss Df (@10GHz) of 0.0057, and a Tg of 295°C.
[0041] <Example 2>
[0042] The manufacturing process is the same as that of Example 1, except that the amount of boron nitride added is different. The amount of boron nitride added is controlled to be 50% by weight of the high thermal conductive polyimide film.
[0043] The polyimide film prepared above has a thermal conductivity of 0.53w / mk, a dielectric loss Df (@10GHz) of 0.0063, and a Tg of 308°C.
[0044] <Example 3>
[0045] Production of polyamic acid
[0046] 35.035 g of 2,2'-bis(trifluoromethyl)diaminobenzidine (TFMB,
[0047] 0.109 mole), add 400 grams of N, N-dimethylacetamide (DMAc), add 11.925 grams of 1,2,4,5-benzenetetracarboxylic anhydride (PMDA, 0.055 mole) after all dissolved, stir and react for 1 hour while the temperature is maintained at 25°C, then add 15.485 grams of 2,2'-diMethyl-4,4'-diaMinobiphenyl (mTB, 0.073 mole), stir until completely dissolved, then slowly add 36.750 grams of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.125 mole), stir for 12 hours to dissolve and react, and the temperature of the solution is maintained at 25°C, then use a small amount of BPDA to adjust the viscosity to 200,000±30,000 cps, and finally obtain a copolymer polyamide acid solution with a solid content of 20wt%.
[0048] Preparation of thermal conductive particle slurry:
[0049] Boron nitride with a particle size distribution of 0.2um-15um was selected and mixed with DMAc to control the solid content of the boron nitride to 20wt%, and then 1.1wt% of polyamic acid was added to the weight of the boron nitride, and the mixture was evenly mixed and then dispersed.
[0050] Preparation of polyimide film
[0051] The above-mentioned polyamic acid is taken to add boron nitride slurry, and the boron nitride content of the high thermal conductivity polyimide film is adjusted by the amount of boron nitride slurry used, and the amount of boron nitride added is controlled to be 25% by weight of the high thermal conductivity polyimide film. After the polyamic acid and boron nitride are evenly mixed, catalysts acetic anhydride and picoline are added to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and lateral shrinkage is performed (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the lateral shrinkage ratio, that is, the wet film width: the dry film width is controlled to be 1:0.80.
[0052] The polyimide film prepared above has a thermal conductivity of 0.42w / mk, a dielectric loss Df (@10GHz) of 0.0064, and a Tg of 313°C.
[0053] <Example 4>
[0054] The manufacturing process is the same as that of Example 3, except that the amount of boron nitride added is different. The amount of boron nitride added is controlled to be 50% by weight of the high thermal conductive polyimide film.
[0055] The polyimide film prepared above has a thermal conductivity of 0.56w / mk, a dielectric loss Df (@10GHz) of 0.0068, and a Tg of 321°C.
[0056] <Example 5>
[0057] Preparation of copolymerized polyamic acid
[0058] 20.127 g of 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB, 0.063 mole) was added to 400 g of N,N-dimethylacetamide (DMAc), and after it was completely dissolved, 13.049 g of 1,2,4,5-benzenetetracarboxylic anhydride (PMDA, 0.060 mole) was added, and the reaction was stirred for 1 hour while the temperature was maintained at 25°C. Then 8.631 g of p-phenylenediamine (PDA, 0.080 mole) was added and stirred until it was completely dissolved. Then 11.741 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.040 mole), after stirring and reacting for 1 hour and maintaining the temperature at 25°C, 5.431 g of 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB, 0.017 mole) was slowly added, and then 11.666 g of 1,3-Bis 1,3-bis(4'-aminophenoxy)benzene (TPER, 0.040 mole) was slowly added and stirred until completely dissolved, and then 26.418 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.090 mole) was slowly added and stirred for 12 hours to allow it to dissolve and react, and the temperature of the solution was maintained at 25°C, and then a trace amount of BPDA was used to adjust the viscosity to 200,000±30,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20wt% was obtained.
[0059] Preparation of thermal conductive particle slurry:
[0060] Boron nitride with a particle size distribution of 0.2um-15um was selected and mixed with DMAc to control the solid content of the boron nitride to 20wt%, and then 1.1wt% of polyamic acid was added to the weight of the boron nitride, and the mixture was evenly mixed and then dispersed.
[0061] Preparation of polyimide film
[0062] The above-mentioned polyamic acid is taken to add boron nitride slurry, and the boron nitride content of the high thermal conductivity polyimide film is adjusted by the amount of boron nitride slurry used, and the amount of boron nitride added is controlled to be 25% by weight of the high thermal conductivity polyimide film. After the polyamic acid and boron nitride are evenly mixed, catalysts acetic anhydride and picoline are added to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and lateral shrinkage is performed (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the lateral shrinkage ratio, that is, the wet film width: the dry film width is controlled to be 1:0.80.
[0063] The polyimide film prepared above has a thermal conductivity of 0.47w / mk, a dielectric loss Df (@10GHz) of 0.0056, and a Tg of 350°C.
[0064] <Example 6>
[0065] The manufacturing process is the same as that of Example 5, except that the amount of boron nitride added is different. The amount of boron nitride added is controlled to be 50 wt % of the weight fraction of the high thermal conductive polyimide film.
[0066] The polyimide film prepared above has a thermal conductivity of 0.61w / mk, a dielectric loss Df (@10GHz) of 0.0064, and a Tg of 362°C.
[0067] <Comparative Example 1>
[0068] Preparation of polyamic acid solution
[0069] 11.898 grams of p-phenylene diamine (PDA, 0.0110 mole) was added with 400 grams of N, N-dimethylacetamide (DMAc). After all the DMAc was dissolved, 16.186 grams of 3,3',4,4'-biphenyltetracarboxylicdianhydride (BPDA, 0.055 mole) was added. The mixture was stirred for 1 hour and the temperature was maintained at 25°C. Then 23.358 grams of 2,2'-diMethyl-4,4'-diaMinobiphenyl (m-Tolidine, 0.110 mole) was added and stirred until the mixture was completely dissolved. Then 47.586 grams of BPDA, 0.1161 mole, was slowly added and stirred for 12 hours until the mixture was dissolved and reacted. The temperature of the solution was maintained at 25°C. Then a small amount of BPDA was used to adjust the viscosity to 200,000±30,000 cps. Finally, a copolymerized polyamide acid solution with a solid content of 20 wt% was obtained.
[0070] Preparation of polyimide film
[0071] The catalysts acetic anhydride and picoline are added to the above copolymerized polyamic acid solution to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and shrunk in the transverse axis (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the transverse shrinkage ratio is controlled, that is, the wet film width: the dry film width = 1:0.80.
[0072] No thermally conductive particles were added to this comparative example.
[0073] The polyimide film prepared above has a thermal conductivity of 0.26w / mk, a dielectric loss Df (@10GHz) of 0.0054, and a Tg of 285°C.
[0074] <Comparative Example 2>
[0075] 35.035 g of 2,2'-bis(trifluoromethyl)diaminobenzidine (TFMB,
[0076] 0.109 mole), add 400 grams of N, N-dimethylacetamide (DMAc), add 11.925 grams of 1,2,4,5-benzenetetracarboxylic anhydride (PMDA, 0.055 mole) after all dissolved, stir and react for 1 hour while the temperature is maintained at 25°C, then add 15.485 grams of 2,2'-diMethyl-4,4'-diaMinobiphenyl (mTB, 0.073 mole), stir until completely dissolved, then slowly add 36.750 grams of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.125 mole), stir for 12 hours to dissolve and react, and the temperature of the solution is maintained at 25°C, then use a small amount of BPDA to adjust the viscosity to 200,000±30,000 cps, and finally obtain a copolymer polyamide acid solution with a solid content of 20wt%.
[0077] Preparation of polyimide film
[0078] The catalysts acetic anhydride and picoline are added to the above copolymerized polyamic acid solution to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and shrunk in the transverse axis (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the transverse shrinkage ratio is controlled, that is, the wet film width: the dry film width = 1:0.80.
[0079] No thermally conductive particles were added to this comparative example.
[0080] The polyimide film prepared above has a thermal conductivity of 0.20w / mk, a dielectric loss Df (@10GHz) of 0.0063, and a Tg of 305°C.
[0081] <Comparative Example 3>
[0082] Preparation of polyamic acid solution
[0083] 20.127 g of 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB, 0.063 mole) was added to 400 g of N,N-dimethylacetamide (DMAc), and after it was completely dissolved, 13.049 g of 1,2,4,5-benzenetetracarboxylic anhydride (PMDA, 0.060 mole) was added, and the reaction was stirred for 1 hour while the temperature was maintained at 25°C. Then 8.631 g of p-phenylenediamine (PDA, 0.080 mole) was added and stirred until it was completely dissolved. Then 11.741 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.040 mole), after stirring and reacting for 1 hour and maintaining the temperature at 25°C, 5.431 g of 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB, 0.017 mole) was slowly added, and then 11.666 g of 1,3-Bis(4-aminophenoxy)benzene (TPER, 0.040 mole) was slowly added and stirred until completely dissolved, and then 26.418 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.090 mole) was slowly added and stirred for 12 hours to allow it to dissolve and react, and the temperature of the solution was maintained at 25°C, and then a trace amount of BPDA was used to adjust the viscosity to 200,000±30,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20wt% was obtained.
[0084] Preparation of polyimide film
[0085] The catalysts acetic anhydride and picoline are added to the above copolymerized polyamic acid solution to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and shrunk in the transverse axis (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the transverse shrinkage ratio is controlled, that is, the wet film width: the dry film width = 1:0.80.
[0086] No thermally conductive particles were added to this comparative example.
[0087] The polyimide film prepared above has a thermal conductivity of 0.19w / mk, a dielectric loss Df (@10GHz) of 0.0054, and a Tg of 340°C.
[0088] <Comparative Example 4>
[0089] Preparation of polyamic acid solution
[0090] 47.847 g of 4,4'-diaminodiphenyl ether (ODA, 0.239 mole) was added with 400 g of N,N-dimethylacetamide (DMAc). After all the DMAc was dissolved, 51.371 g of 1,2,4,5-benzenetetracarboxylic anhydride (PMDA, 0.236 mole) was added. The temperature was controlled at 25°C during the addition. The reaction was stirred for 24 hours and the temperature was maintained at 25°C. Then, a small amount of PMDA was used to adjust the viscosity to 200,000±30,000 cps, and finally a copolymer polyamide acid solution with a solid content of 20wt% was obtained.
[0091] Preparation of polyimide film
[0092] The catalysts acetic anhydride and picoline are added to the above copolymerized polyamic acid solution to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and shrunk in the transverse axis (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the transverse shrinkage ratio is controlled, that is, the wet film width: the dry film width = 1:0.80.
[0093] No thermally conductive particles were added to this comparative example.
[0094] The polyimide film prepared above has a thermal conductivity of 0.23w / mk, a dielectric loss Df (@10GHz) of 0.0244, and a Tg of 385°C.
[0095] <Comparative Example 5>
[0096] Preparation of polyamic acid solution
[0097] 40.468 g of 4,4'-diaminodiphenyl ether (ODA, 0.202 mole) was added to 400 g of N,N-dimethylacetamide (DMAc), and after all were dissolved, 58.639 g of 3,3',4,4'-biphenyltetracarboxylicdianhydride (BPDA, 0.199 mole) was added. The temperature was controlled at 25°C during the addition. The reaction was stirred for 24 hours and the temperature was continuously maintained at 25°C. Then, a small amount of BPDA was used to adjust the viscosity to 200,000±30,000 cps, and finally a copolymer polyamide acid solution with a solid content of 20wt% was obtained.
[0098] Preparation of polyimide film
[0099] The catalysts acetic anhydride and picoline are added to the above copolymerized polyamic acid solution to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and shrunk in the transverse axis (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the transverse shrinkage ratio is controlled, that is, the wet film width: the dry film width = 1:0.80.
[0100] No thermally conductive particles were added to this comparative example.
[0101] The polyimide film prepared above has a thermal conductivity of 0.31w / mk, a dielectric loss Df (@10GHz) of 0.0093, and a Tg of 380°C.
[0102] <Comparative Example 6>
[0103] Preparation of polyamic acid solution
[0104] Its preparation procedure is the same as that of Comparative Example 4
[0105] Preparation of thermal conductive particle slurry:
[0106] Boron nitride with a particle size distribution of 0.2um-15um was selected and mixed with DMAc to control the solid content of the boron nitride to 20wt%, and then 1.1wt% of polyamic acid was added to the weight of the boron nitride, and the mixture was evenly mixed and then dispersed.
[0107] Preparation of polyimide film
[0108] The above-mentioned polyamic acid is taken to add boron nitride slurry, and the boron nitride content of the high thermal conductivity polyimide film is adjusted by the amount of boron nitride slurry used, and the amount of boron nitride added is controlled to be 50wt% of the weight fraction of the high thermal conductivity polyimide film. After the polyamic acid and boron nitride are evenly mixed, catalysts acetic anhydride and picoline are added to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and lateral shrinkage is performed (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the lateral shrinkage ratio, that is, the wet film width: the dry film width is controlled to be 1:0.80.
[0109] The polyimide film prepared above has a thermal conductivity of 0.48w / mk, a dielectric loss Df (@10GHz) of 0.0235, and a Tg of 405°C.
[0110] <Comparative Example 7>
[0111] Preparation of polyamic acid solution
[0112] Its preparation procedure is the same as that of Comparative Example 5
[0113] Preparation of thermal conductive particle slurry:
[0114] Boron nitride with a particle size distribution of 0.2um-15um was selected and mixed with DMAc to control the solid content of the boron nitride to 20wt%, and then 1.1wt% of polyamic acid was added to the weight of the boron nitride, and the mixture was evenly mixed and then dispersed.
[0115] Preparation of polyimide film
[0116] The above-mentioned polyamic acid is taken to add boron nitride slurry, and the boron nitride content of the high thermal conductivity polyimide film is adjusted by the amount of boron nitride slurry used, and the amount of boron nitride added is controlled to be 50% by weight of the high thermal conductivity polyimide film. After the polyamic acid and boron nitride are evenly mixed, catalysts acetic anhydride and picoline are added to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and lateral shrinkage is performed (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the lateral shrinkage ratio, that is, the wet film width: the dry film width is controlled to be 1:0.80.
[0117] The polyimide film prepared above has a thermal conductivity of 0.78w / mk, a dielectric loss Df (@10GHz) of 0.0098, and a Tg of 405°C.
[0118] Comparative Example 8
[0119] The manufacturing process is the same as that of Example 1, except that the amount of boron nitride added is different. The amount of boron nitride added is controlled to be 60 wt % of the weight fraction of the high thermal conductive polyimide film.
[0120] The polyimide film prepared above has a thermal conductivity of 0.65w / mk, a dielectric loss Df (@10GHz) of 0.0076, and a Tg of 315°C.
[0121] <Comparative Example 9>
[0122] Production of polyamic acid
[0123] 20.443 grams of p-phenylene diamine (PDA, 0.189 mole) was added to 400 grams of N, N-dimethylacetamide (DMAc). After all the DMAc was dissolved, 27.809 grams of 3, 3', 4, 4'-biphenyltetracarboxylicdianhydride (BPDA, 0.095 mole) was added. The mixture was stirred for 1 hour and the temperature was maintained at 25°C. Then 10.033 grams of 2, 2'-diMethyl-4, 4'-diaMinobiphenyl (m-Tolidine, 0.047 mole) was added and stirred until the mixture was completely dissolved. Then 40.671 grams of BPDA, 0.138 mole, was slowly added and stirred for 12 hours until the mixture was dissolved and reacted. The temperature of the solution was maintained at 25°C. Then a small amount of BPDA was used to adjust the viscosity to 200,000 ± 30,000 cps. Finally, a copolymerized polyamide acid solution with a solid content of 20 wt% was obtained.
[0124] Preparation of imide film
[0125] The catalysts acetic anhydride and picoline are added to the above copolymerized polyamic acid solution to make the molar ratio of polyamic acid: acetic anhydride: picoline = 1:2.7:1.2, and coated on a carrier for low-temperature baking (less than 150°C) (the film width is the wet film width at this time), and then peeled off and shrunk in the transverse axis (the film width is the dry film width at this time), and baked at a high temperature of more than 300°C to form a polyimide film, and the transverse shrinkage ratio is controlled, that is, the wet film width: the dry film width = 1:0.80.
[0126] No thermally conductive particles were added to this comparative example.
[0127] The polyimide film prepared above has a thermal conductivity of 0.28w / mk, a dielectric loss Df (@10GHz) of 0.0110, and a Tg of 340°C.
[0128] Example and comparative example test result table:
[0129]
[0130] It can be seen from the embodiments and comparative examples that comparative examples 1-3 have no thermally conductive particles added, resulting in thermal conductivities of all of them being below 0.35 w / mk.
[0131] Although thermal conductive particles are added in Comparative Examples 6-7, no improved formula is added, resulting in good thermal conductivity but too high dielectric loss (@10 GHz), with Df greater than 0.007.
[0132] In Comparative Examples 4-5, not only because no thermal conductive particles are added, but also because there is no improved formula design, the dielectric loss (@10GHz) is above 0.007 and the thermal conductivity is less than 0.35w / mk.
[0133] In Comparative Example 8, the amount of thermally conductive particles added exceeds 50 wt %. Although the thermal conductivity is better, the dielectric loss (@10 GHz) is increased by more than 0.007 due to the excessive amount of thermally conductive particles.
[0134] In Comparative Example 9, although the improved formula 4,4'-diamino-2,2'-dimethylbiphenyl (m-TB) is introduced, the addition amount thereof is insufficient (less than 30 mol%), resulting in excessive dielectric loss (@10 GHz) (higher than 0.007).
[0135] The description of the above embodiments is only used to help understand the method and core idea of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.
Claims
1. A high thermal conductivity polyimide film with low dielectric loss, characterized in that: include: At least one dianhydride, including: benzophenonetetracarboxylic dianhydride; At least one diamine, comprising the chemical formula: One or more of the compounds of Thermally conductive particles, the weight of which accounts for 25 to 50 wt% of the highly thermally conductive polyimide film; Among them, the molar number of the benzophenonetetracarboxylic dianhydride accounts for more than 30% of the total molar number of the dianhydride, R in the chemical formula of the diamine includes: -CH3, and the molar number of the diamine in which R is -CH3 must account for more than 30% of the total molar number of the diamine, so that the low dielectric loss and high thermal conductivity polyimide film has a. dielectric loss tangent Df (@10GHz) is less than 0.007 and thermal conductivity is greater than 0.35W / mk.
2. The high thermal conductivity polyimide film with low dielectric loss according to claim 1, wherein: R in the chemical formula of the diamine may also be -CF3.
3. The high thermal conductivity polyimide film with low dielectric loss according to claim 1, wherein: The diamine further includes: p-phenylenediamine and / or 1,3-bis(4'-aminophenoxy)benzene.
4. The high thermal conductivity polyimide film with low dielectric loss according to claim 1, wherein: The dianhydride component also includes 1,2,4,5-benzenetetracarboxylic anhydride.
5. The high thermal conductivity polyimide film with low dielectric loss according to claim 1, wherein: The thermally conductive particles are selected from BN, AlN, Al2O3, SiC, and SiO2.
6. A method for manufacturing a high thermal conductivity polyimide film with low dielectric loss, comprising: A copolymerized polyamic acid is provided, wherein the copolymerized polyamic acid comprises at least one anhydride and a dianhydride, including: Benzophenone tetracarboxylic dianhydride; At least one diamine, comprising the chemical formula: One or more of the compounds; and Wherein, R in the chemical formula includes: -CH3; The weight of the thermally conductive particles is 25-50 wt% of the high thermally conductive polyimide film; and the copolymerized polyamic acid is added with a dehydrating agent and a catalyst. The dehydrating agent is acetic anhydride, and the catalyst is methyl pyridine and isoquinoline; the added amount of the dehydrating agent is more than 2.7 equivalents, and the added amount of the catalyst is more than 1.2 equivalents.
7. The manufacturing method according to claim 6, wherein: The R also includes -CF3.
8. The manufacturing method according to claim 6, wherein: The diamine further includes: p-phenylenediamine and / or 1,3-bis(4'-aminophenoxy)benzene (TPER).
9. The manufacturing method according to claim 6, wherein: The dianhydride also includes 1,2,4,5-pyromellitic anhydride.
Citation Information
Cited By
Polyimide film and laminates using the film
TWI944959B
